Acupuncture treatment of vascular cognitive impairment through peripheral nerve stimulation pathway: a scoping review - Yang, Xinming; Li, Bo; Wu, Linna; Cui, Ying (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis study aims to explore the central effects of acupuncture on vascular cognitive impairment (VCI) through peripheral nerve stimulation.MethodsThis scoping review followed the methodological framework proposed by Arksey and O’Malley and the PRISMA-ScR guidelines. A comprehensive search of databases, including PubMed, Web of Science, MEDLINE, and Embase, was conducted, including 79 studies on acupuncture interventions for VCI. Acupoints and their underlying anatomical structures related to peripheral nerves were summarized, and the potential pathways of acupuncture effects via different peripheral nerves were explored.ResultsThe results showed that acupuncture, by stimulating specific acupoints on the head, face, torso, and limbs, significantly affects peripheral nerve networks, including the cervical, lumbar, and sacral plexuses, thoracic nerves, vagus nerve, trigeminal nerve and its branches. The nerve stimulation effects of acupuncture can enhance the regulation of cerebral blood flow, modulate neuroimmune responses, improve brain function, and promote neuroplasticity through multiple central nervous system pathways, ultimately improving cognitive function and treating VCI.ConclusionAcupuncture is a treatment modality that influences the central nervous system through peripheral nerve stimulation to treat VCI. A deeper understanding of the central effects induced by acupuncture-triggered neural reflexes can contribute to the improvement of existing therapies and help elucidate the scientific principles underlying acupuncture’s therapeutic effects.